Stevens-Johnson Syndrome Following Vancomycin and Linezolid: A Real-World Analysis of Post-Marketing Surveillance Data - Ni, Ming; Yin, Xue-Dong; Hu, Wen-Juan; Zeng, Na; Zhao, Bin; Li, Zhi-Ling (Frontiers in Pharmacology, 2022)
Background Although Stevens-Johnson Syndrome (SJS) has been reported as a serious adverse effect in patients treated with Vancomycin or Linezolid (Linezolid), there are still few real-world studies to compare the specific differences in the adverse effects of nephrotoxicity. Methods According to the FDA's Adverse Event Reporting System (FAERS), from January 2004 to July 2021, the data of suspected SJS after the use of vancomycin and linezolid were analyzed by imbalance and Bayesian analysis. The onset time, fatality rate and hospitalization rate of vancomycin-associated SJS and linezolid-associated SJS were also investigated. Results 276 cases of vancomycin-related SJS reports and 63 cases of linezolid-related SJS reports were identified. These two drugs are more common in middle-aged patients (45-64 years) than other age groups, and less common in underage children (<18). Among them, linezolid-related SJS is more common in middle-aged and elderly patients (45-74 years old) than other groups. Except for unspecified data, in vancomycin-associated SJS cases, there are more men than women (49.28% vs 43.84%), while in linezolid-associated SJS cases, the proportion of men and women is almost equal (44.44%). From the point of view of the areas where adverse reactions were reported, about 1/2 of the reports on Vancomycin-related SJS came from North America, and 1/3 of the reports came from Europe. The median onset time of Linezolid-related SJS was 5 days (interquartile range [IQR] 2-7.75), which was significantly earlier than that of Vancomycin-related SJS (12 days, IQR 4-20) (Mann-Whitney test, p<0.0001).There were no significant differences in mortality and hospitalization rates after vancomycin and linezolid caused SJS. Conclusions The analysis of FAERS data provides a more accurate profile on the incidence and prognosis of SJS after Vancomycin and Linezolid treatment, enabling continued surveillance and timely intervention in patients at risk of SJS using these drugs.